HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KECEMASAN MENGHADAPI PERTANDINGAN PADA ATLET KARATE UNIVERSITAS NEGERI JAKARTA - Ibrahim, Saipulloh; Muh. Yasa; Agus Kurniadi; La Ode Ahmad Yusran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between self-confidence and anxiety in facing competition among karate athletes at the State University of Jakarta. Anxiety in facing competition is a common psychological problem that can reduce athletes' performance, while self-confidence is believed to be one of the internal factors that influence it. This research used a quantitative approach with a correlational method. The sample consisted of 30 karate athletes selected through total sampling. Data were collected using a self-confidence scale and a competition anxiety scale, then analyzed using the Pearson Product Moment correlation after fulfilling the normality and linearity prerequisite tests. The results showed a correlation coefficient of -0.818 with a significance value of 0.000 (< 0.05), which means there is a significant negative relationship between self-confidence and competition anxiety. The coefficient of determination of 66.9% indicates that self-confidence contributes substantially to competition anxiety. Thus, the higher the athlete's self-confidence, the lower the anxiety in facing competition, and vice versa.